Heart Rate Variability Analysis in Young Obese Individuals (International Journal of Physiology, 2019)
IntroductionObesity is associated with marked cardiorespiratory changes. In obese individuals there occurs an increase in heart rate, systolic blood pressure and cardiac output up to 15%. These changes are thought to occur as a result of changes in autonomic activity. Among the available noninvasive techniques for assessing autonomic status, heart rate variability has emerged as a simple non-invasive method to evaluate sympatho-vagal balance.Materials and MethodHeart Rate Variability analysis was done in 30 young obese individuals and compared with 30 age and gender matched individuals with normal BMIResultsIn obese individuals, the SDNN was significantly higher than in controls. LF and LF/HF values of obese individuals were significantly higher than those of controls but their HF values were lower.ConclusionHRV analysis shows sympathetic overactivity and parasympathetic blunting in young obese individuals.